Influence of La substitution on local structural and photoluminescence properties of SrTiO3:Pr phosphor - Deltreggia, Lucas Angelini [UNESP]; Bernardi, Maria Inês Basso; Mesquita, Alexandre [UNESP] (Elsevier, 2018)
Pr3+-doped perovskite-based SrTiO3 phosphors have been developed as a potential red phosphor. In this paper, we report the substitution of La3+ ions for Sr2+ ions in order to promote Sr vacancies to further enhance photoluminescence. Given that the La content increases, an enhancement in the intensity of all emissions is observed, mainly for 1D2–3H4 and 3P0–3H6 transitions. This enhancement of photoluminescence emissions is associated with disorder in the lattice caused by La incorporation. Raman measurements and X-ray absorption near edge structure (XANES) spectra at the Ti K-edge identify this disorder as a function of the La content.